Design and Implementation of a YARP Device Driver Interface: The Depth-Sensor Case - Cardellino, Alberto; Ruzzenenti, A.; Natale, L. (Frontiers in Robotics and AI, 2018)
This work illustrates the design phases leading to the development of a new YARP device interface along with its client/server implementation. In order to obtain a smother integration and a more reliable software usability, while avoiding common errors during the design phases, a new interface is created in the YARP network when a new family of devices is introduced.